Urbanization and rural development in the People's Republic of China - Zhao Chen; Ming Lu; Pengtu Ni (Asian Development Bank Institute (ADBI), 2016)
This paper presents research findings on how urbanization enhances productivity and economic growth in both urban and rural sectors. Through agglomeration effects, employment opportunities and income levels can largely increase. In addition, the mechanisms of sharing, matching, and learning are much stronger in cities, especially large cities. However, in the People's Republic of China (PRC), urbanization lags far behind industrialization. Institutional barriers against rural-to-urban and interregional migration, such as the hukou system, have reduced the ability of urban growth to absorb rural labor. As for rural development, urbanization has propelled agricultural productivity, rural income, and consumption levels. Moreover, agricultural productivity is driven to a large extent by capital accumulation, through capital deepening and remittance. Agricultural organizations, urbanization, and outflow of migrant workers make it possible for large-scale production and agricultural mechanization to occur.
Keywords: O14; R11; E23; 330; Urbanization; rural development; PRC; China; hukou system; productivity; economic growth